3‐2: Distinguished Paper: An 18 Megapixel 4.3″ 1443 ppi 120 Hz OLED Display for Wide Field of View High Acuity Head Mounted Displays. Issue 1 (30th May 2018) - Vieri, Carlin; Lee, Grace; Balram, Nikhil; Jung, Sang Hoon; Yang, Joon Young; Yoon, Soo Young; Kang, In Byeong
Abstract : We developed and fabricated the world's highest resolution (18 megapixel, 1443 ppi) OLED on glass display panel. The design uses a white OLED with color filter structure for high density pixelization and an n‐type LTPS backplane for faster response time than mobile phone displays. A custom high bandwidth driver IC was fabricated. We developed a foveated pixel pipeline appropriate for VR and AR applications, especially mobile systems.